‘If you yourself you are the poor quality, it means you are delivering the poorest quality of service’ – understanding health care workers’ perceptions about quality of care during facility-based deliveries in two rural hospitals in Uganda - Srovin,Masa (2024)
Introduction: Many countries in the world are still facing high maternal mortality rates and women still die due to preventable pregnancy- and birth-related causes. This could be prevented with an improvement in the quality of care and yet many countries, especially in the rural areas, have challenges in doing so. In order to understand why is care given in certain way, more qualitative studies need to be done to understand what is a quality care for health care providers and what challenges are they facing. This study aims to explore the health care workers’ perception on the quality of care during childbirth in Uganda. Methods: A qualitative approach was taken by conducting six focus group discussions with 25 midwives from the two health facilities in rural western Uganda. Collected data was analyzed with qualitative content analysis and interpreted in the context of the Ugandan rural areas. Results: Midwives perceived quality care during birth as something that goes beyond just the act of birth. Three main themes have emerged from analysis: ‘achieving quality care is seen as an individual process that starts long before pregnancy and ends with healthy and satisfied mother and baby in postpartum period’, ‘feeling limited power as midwives over changing and improving quality of care in their facility’ and ‘wanting to be seen, heard, taken care of and continuously educated to be able to provide quality care’. Discussion: Quality care during birth is seen as holistic care that is affected by care before pregnancy, childbirth and after. Because of many things that they believe influence the care, midwives often feel like they have limited power in improving the quality in their facility. What they believe it is giving them the most power to provide good care is feeling supported and well-taken care of by facility’s management and being provided with further education to enhance their knowledge. Conclusion: Health care workers are the ones in the frontline of fighting the high rates of maternal mortality and they should be listened to and assisted in any way they need in order to provide a good quality of care during birth. Keywords: Childbirth, Uganda, quality care, midwives
Keywords: Childbirth; Uganda; quality care; midwives